2020
DOI: 10.1111/aji.13349
|View full text |Cite
|
Sign up to set email alerts
|

Milk exosomes: A biogenic nanocarrier for small molecules and macromolecules to combat cancer

Abstract: Exosomes are unique biogenic nanocarriers of endocytic origin that are generated from most of the cells and found in biofluids like milk, plasma, saliva, and urine. Bovine milk represents the largest and an economic source for the production of exosomes. In recent past, the utility of the milk exosomes as drug carriers is intensified. Exosomes are emerging for delivery of both small and large therapeutics due to their biocompatibility. In this article, we highlighted the various exosomal isolation techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 90 publications
2
29
0
Order By: Relevance
“…Milk EVs may play an important role in drug delivery because of their beneficial properties, such as mass production due to the industrial scale of milk, passage of biological barriers, resistance in the digestive tract, etc., and supporting studies have been reported ( Adriano et al, 2021 ; Kandimalla et al, 2021b ; Sedykh et al, 2020 ; Zhong et al, 2021 ). An approach to efficiently treat diseases such as cancer by loading small interfering RNA or drugs into bovine milk EVs is being performed.…”
Section: Drug Delivery As Biological Carrier Of Bovine Milk-derived E...supporting
confidence: 86%
“…Milk EVs may play an important role in drug delivery because of their beneficial properties, such as mass production due to the industrial scale of milk, passage of biological barriers, resistance in the digestive tract, etc., and supporting studies have been reported ( Adriano et al, 2021 ; Kandimalla et al, 2021b ; Sedykh et al, 2020 ; Zhong et al, 2021 ). An approach to efficiently treat diseases such as cancer by loading small interfering RNA or drugs into bovine milk EVs is being performed.…”
Section: Drug Delivery As Biological Carrier Of Bovine Milk-derived E...supporting
confidence: 86%
“…Due to their high biocompatibility and stability, milk exosomes have been proposed as promising vehicles for the delivery of hydrophilic and lipophilic bioactive compounds [ 216 ]. In contraposition to artificial delivery systems, these formulations might present lower immunogenicity, superior bioavailability, increased capacity to cross biological barriers, and the ability to confer protection against harsh conditions, thus improving the biological effects of delivered molecules while reducing their potential toxicity [ 32 , 59 , 217 , 218 ]. Specifically, the use of milk exosomes to deliver epicatechin gallate (ECG), a naturally occurring polyphenolic compound with neuroprotective properties, was shown to improve its antioxidative and antiapoptotic effects while inhibiting autophagy in a rotenone-induced model of Parkinson’s disease in vitro, compared to the incubation with free ECG [ 217 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To establish milk exosomes as ingredients and delivery vehicles, it is mandatory to overcome some limitations of current isolation and characterization methods, mainly those related to the inability to produce inexpensive and large-scale quantities of milk exosomes [ 40 ]. For instance, novel microfluidics-based techniques yield high purity exosomes and are automatable but lack scalability and high sample capacity [ 59 , 218 ]. Optimization of current ultracentrifugation and filtration protocols (i.e., TFF), as well as the use of mixed approaches, including combinations of different characterization techniques, might be best suited for the large-scale production of high-quality milk exosomes [ 40 , 227 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Exosomes are released from essentially all cell types and are present in all bodily fluids like blood, urine, saliva, amniotic fluid, lymphatic fluid and milk etc. [15,16]. Unlike other nanoparticulate systems, exosomes possess special proteins in their membrane surface proteins that may help in the endocytosis, which, in turn, promotes the delivery of tethered content [17,18].…”
Section: Introductionmentioning
confidence: 99%